2016
DOI: 10.1111/jep.12597
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of granulocyte colony‐stimulating factor prophylaxis in chemotherapy‐induced febrile neutropenia among breast cancer and Non‐Hodgkin's lymphoma patients under Taiwan's national health insurance system

Abstract: Primary but not secondary prophylactic use of G-CSF was cost-effective in CIFN in breast cancer and NHL patients under Taiwan's NHI system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Our findings that primary prophylaxis is cost-effective in patients with breast cancer are consistent with previous studies [ 19 21 , 44 , 45 ]. For example, a previous study conducted in Taiwan evaluated the cost-effectiveness of short-acting G-CSFs in breast cancer patients and found that primary prophylaxis was cost-effective and secondary prophylaxis was a dominated strategy [ 45 ]. While the previous study only evaluated the cost-effectiveness of short-acting G-CSFs, our study further incorporated long-acting G-CSF and biosimilars into the evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings that primary prophylaxis is cost-effective in patients with breast cancer are consistent with previous studies [ 19 21 , 44 , 45 ]. For example, a previous study conducted in Taiwan evaluated the cost-effectiveness of short-acting G-CSFs in breast cancer patients and found that primary prophylaxis was cost-effective and secondary prophylaxis was a dominated strategy [ 45 ]. While the previous study only evaluated the cost-effectiveness of short-acting G-CSFs, our study further incorporated long-acting G-CSF and biosimilars into the evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…A study using Taiwan's NHI database showed positive effectiveness and cost-effectiveness results for primary prophylactic use of G-CSF in patients with non-Hodgkin's lymphoma. Primary prophylactic G-CSF was not only effective in preventing neutropenia with a 74% reduction in incidence, but also reduced the incidence of febrile neutropenia by 83% at an incremental cost of US$52 per cycle to reduce 1% of febrile neutropenia [45]. From the perspective of Taiwan's healthcare payers, the incremental cost-effectiveness ratio was well below the willingness to pay (WTP) threshold of three times Taiwan's 2015 gross domestic product per capita (US$22,464) [46,47].…”
Section: Discussionmentioning
confidence: 99%